Pengembangan Media Video Animasi untuk Meningkatkan Kemampuan Menganalisis Bentuk-Bentuk Interaksi Manusia dengan Lingkungan - Nadidah, Mu'fidatus Sayyidan; Mukmin, Bagus Amirul; Laila, Alfi (Jurnal Likhitaprajna, 2024)
This research aims 1) to determine the validity of animated video media of human interaction with the environment in class V of SD Negeri Bulusari. 2) Knowing the effectiveness of animated video media for human interaction with the environment in class V of SD Negeri Bulusari. 3) Knowing the practicality of animated video media for human interaction with the environment in class V of SD Negeri Bulusari. This research uses the Research and Development (R&D) development method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with research subjects namely 5 students in class V of SD Negeri Bulusari 2 and SD Negeri Bulusari 3 with 23 students. This research uses data analysis techniques in the form of media expert validation questionnaire instruments, material expert validation questionnaires, teacher response questionnaires, student response questionnaires, and student learning outcomes in the form of pre-tests and post-tests. The results of this development research are 1) The animated video learning media received an average score of 94% from media expert validation and material expert validation, meaning that the learning media created is very valid for use without revision. 2) The animated video learning media in the limited trial got an average score of 88% and in the extensive trial it got an average score of 95%, meaning that the learning media created was very practical to use. These scores were obtained from teacher questionnaires and student questionnaires in limited trials and extensive trials. (3) The animated video learning media was stated to be very effective, because students' classical completion results in limited trials and extensive trials were 100%.